Experience in management of pregnant women with the pathology of nervous system at the consultation and diagnostic department in a day hospital - E. V. Beliyaeva; L. V. Lapshina; E. V. Shaposhnikova; M. V. Beliyaeva (Лечащий Врач)
The pregnancy course in women with the nervous system pathology can have a high risk of maternal and perinatal complications. The management of the women in such condition requires a specialist to provide an on-time diagnosis and accurate follow-up supervision of the gestational process with the complex interdisciplinary approach. Our experience in management of pregnant women with the pathology of nervous system at the consultation-and-diagnostic department in a hospital is presented.